Preparation of two dimensional layered double hydroxide nanosheets and their applications. (2nd August 2017) - Yu, Jingfang; Wang, Qiang; O'Hare, Dermot; Sun, Luyi
Abstract : This review summarizes pathways to obtain LDH nanosheets for various applications, provides an overview of the current understanding of mechanistic studies, and promotes a better understanding of the fundamental chemistry, which will in turn be beneficial for the wider scientific community, and will present potential future directions of the research areas. Abstract : Layered double hydroxides (LDHs) with their highly flexible and tunable chemical composition and physical properties have attracted tremendous attention in recent years. LDHs have found widespread application as catalysts, anion exchange materials, fire retardants, and nano-fillers in polymer nanocomposites. The ability to exfoliate LDHs into ultrathin nanosheets enables a range of new opportunities for multifunctional materials. In this review we summarize the current available LDH exfoliation methods. In particular, we highlight recent developments for the direct synthesis of single-layer LDH nanosheets, as well as the emerging applications of LDH nanosheets in catalyzing oxygen evolution reactions and preparing light emitting devices, supercapacitors, and flame retardant nanocomposites.